Age and provenance of the Upper Cretaceous Valdez Group turbidites, Northern Prince William Sound, Alaska - Almonte, Nicholas (Carleton Digital Commons, 2019)
Detrital zircon U-Pb ages from turbidites of the Upper Cretaceous Valdez Group of the Chugach terrane in Prince William Sound, Alaska help demonstrate the complex relationship with the outboard turbidites of the Paleocene-Eocene Orca Group. The Valdez and Orca Groups, while similar in composition, historically have been divided by metamorphic grade, age, and geography. Ten sandstone samples from the Valdez Group were collected from northern Prince William Sound and along the Richardson Highway. Maximum depositional ages (MDAs) of the Valdez Group range from 84.1 to 59.8 Ma and are concentrated in three clusters: 84-78 Ma, 74-65 Ma, and 62-60 Ma. The oldest cluster includes samples that have similar Late Cretaceous populations between 97-79 Ma and Early to Middle Jurassic populations between 197-164 Ma. Six samples in the middle 74-65 Ma cluster have their own sub-cluster and have MDAs between 70-66 Ma with pronounced Late Cretaceous populations between 76-68 Ma. Three samples collected from rocks mapped as the Valdez Group along the Richardson Highway have MDAs between 62-60 Ma, and these have similar MDAs and grain-age distributions to rocks of the lower Orca Group in Prince William Sound. These samples are dominated by zircons with Late Cretaceous zircons between 72-70 Ma and Early Cretaceous zircons between 109-106 Ma. The young samples are Paleocene and are younger than what is traditionally viewed as the age range of the Valdez Group, and thus they present a dilemma. We have two options for the occurrence of Orca Group age-correlative samples in areas mapped as the Valdez Group: 1) the Richardson facies is part of the Valdez Group and is stratigraphically equivalent to the oldest Orca Group (Miners Bay facies); or 2) the Richardson facies is part of the Orca Group and occurs in the Valdez Group as structural slices or was deposited unconformably on top of the Valdez and subsequently folded into the Valdez Group.